Elements of the Historical Model City in the Structures of Selected Tourist European Coastal Cities - PODHORODECKA, Katarzyna; KWIATKOWSKI, Jacek (Journal of Environmental Management and Tourism, 2025)
This paper analyzes selected coastal tourist cities in the Mediterranean region and the Canary Islands. Selected cities were compared with the features of a historical city verified as model cities according to the author's specific methodological key. As part of the application part, a far-reaching relationship between the above two groups of cities was observed and emphasized. The fact of this relationship creates an extremely favorable situation for the development of the tourism industry, as it introduces a synergistic effect for the development of cultural tourism. There is a complementary enrichment of both basic functions and forms of tourism - between active tourism and cultural tourism. This phenomenon may result in an additional extension of the tourist season, which is an invaluable value for hoteliers, restaurateurs and service providers.